Debaryomyces Hansenii: Harnessing its Signification in Kumaun Himalaya’s Traditional Meat Products - Kumar Rai, Arun; Chettri, Arun (Journal of Meat Science, 2026)
The article delves into the prevalence of yeast Debaryomyces hansenii, as identified by using phenotypic identification following the method of Kreger van Rij and Kurtzman and Fell alongside biochemical assays is notably higher in traditionally prepared meat products as compared with other yeast genera from the different pockets of Kumaun Himalayan region. This surveillance is harmonious with the observation from studies carried out on meat products by other researchers across the globe. Despite the traditional preparation methods of meat products adopted by ethnic people of the Himalayas, the occurrence of this yeast plays a significant role in enhancing the shelf life and highlights potential avenues for improving food security in resource-constrained environments. Notably, documenting the indigenous knowledge of traditional meat processing techniques among ethnic groups residing in remote areas of the India-Nepal border is arduous. Understanding the microbial ecology of these items is crucial because it provides insight into the natural processes that support their preservation. The existence of D. hansenii, a yeast that has been detected by biochemistry and phenotypic analysis, is rigorously examined in this paper.